Enhancing ethical behavior in online exams - Bąkała, Anna; Bąkała, Marcin (Annales. Etyka w Życiu Gospodarczym, 2020)
Online exams have become a common tool in the academic didactic process, as well as in most online courses in business. Taking exams in a remote location like home, using ICT tools, brings many challenges to both sides, the learner and the examiner. The aim of this article is to show the challenges in the context of ethical attitudes, trust, and respect for one another. Some results of a broader survey in the form of Computer Aided Web Interviews are presented to highlight students’ opinions and expectations, along with the results of personal interviews with academic teachers. In the final part of the article, recommendations are given. The importance of trust and systematic assessment of learners’ progress is emphasized.